2020
DOI: 10.1111/jssr.12698
|View full text |Cite
|
Sign up to set email alerts
|

The Zeal of the Convert Revisited

Abstract: Social scientists have long been interested in the effects of conversion on religiosity. Drawing on data from the 2014 Pew Religious Landscape Survey, I revisit the zeal of the convert thesis by comparing the religiosity of both converts and cradle members within the main American religious traditions. My findings reveal that converts are not more zealous than lifelong members, in fact, converts tend to have lower levels of religious commitment. Switchers raised in strict denominations do exhibit greater zeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…According to data from the World Values Survey, the proportion of the global population identifying as religious nones doubled over the last forty years, and in Europe that proportion tripled, from 10.5 per cent to 30.2 per cent, over the same period (Balazka, 2020). In the United States, where religious identity is highly unstable (Beider, 2021), the proportion of nones increased at a more rapid pace, rising from about 15 per cent to about 23 per cent of the adult population in the span of only seven years, between and 2014(Pew Research Center, 2012a. While these figures are striking, it is not at all clear what to make of them.…”
Section: Religious Nones: a Global Perspectivementioning
confidence: 99%
“…According to data from the World Values Survey, the proportion of the global population identifying as religious nones doubled over the last forty years, and in Europe that proportion tripled, from 10.5 per cent to 30.2 per cent, over the same period (Balazka, 2020). In the United States, where religious identity is highly unstable (Beider, 2021), the proportion of nones increased at a more rapid pace, rising from about 15 per cent to about 23 per cent of the adult population in the span of only seven years, between and 2014(Pew Research Center, 2012a. While these figures are striking, it is not at all clear what to make of them.…”
Section: Religious Nones: a Global Perspectivementioning
confidence: 99%
“…In some studies with predominantly Christian samples, converts have been found to be more religiously committed and engaged (Pew Research Center, 2009; Suh & Russell, 2015) compared to lifelong believers. However, others have found no difference in R/S between converts and lifelong believers (Beider, 2021).…”
Section: The Zeal Of a Convertmentioning
confidence: 97%
“…Furthermore, childhood socialization influences adult religiosity even in cases of religious switching, with signs of continuity across identity ruptures in the form of a persistent residue of the prior identity (Ebaugh, 1988 ). 1 Thus, converts raised as nones are less religiously committed than are lifelong affiliates, while those raised in strict traditions, such as Evangelical Protestant and historically Black Protestant denominations, tend to be more so (Beider, 2021 ). Childhood affiliation leaves an imprint on adult religiosity (Bullivant, 2016 ; Schwadel et al., 2021 ; Van Tongeren et al., 2021 ), with the effect perhaps more noticeable among disaffiliates.…”
Section: Theoretical Considerations and Hypothesesmentioning
confidence: 99%